Using Pretreatment of Carbon Monoxide Combined with Chlorine Dioxide and Lactic Acid to Maintain Quality of Vacuum-Packaged Fresh Beef - Fei Lyu; Yuliang Zhao; Kejing Shen; Xuxia Zhou; Jianyou Zhang; Yuting Ding (Journal of Food Quality)
Due to microbial growth, beef easily gets corrupt in retail conditions, and the color and quality of the meat will be deteriorated. Therefore, hurdle technology, namely, pretreatment of carbon monoxide (CO), chlorine dioxide, and lactic acid, is used for vacuum-packaged beef to decontaminate beef and increase its quality stability. Beef was pretreated with 100% CO (C1), 100% CO and 50 mg/L chlorine dioxide (C2), and 100% CO and 50 mg/L chlorine dioxide and 30 g/L lactic acid (C3). The untreated samples were used as control (CK). During storage, the a⁎ color parameters of C1, C2, and C3 were significantly higher than that of CK, indicating CO pretreatment is a good way to maintain color appearance of beef, and chlorine dioxide and lactic acid did not affect the color-protecting role of CO on beef. C3 showed the strongest antimicrobial activity with the lowest total viable counts, followed by C2, C1, and CK. Samples in C3 also showed the lowest total volatile basic nitrogen, pH, thiobarbituric acid reactive substance, and metmyoglobin during the mid-late storage. Moreover, C3 can keep beef with higher unsaturated fatty acids. In conclusion, CO pretreatment combined with chlorine dioxide and lactic acid displayed efficient antimicrobial and color-stability activity for vacuum-packaged beef. It would be a potential way to use pretreatment of CO combined with chlorine dioxide and lactic acid to maintain the quality of vacuum-packaged beef.